Differential Expression of Acid – Sensing Ion Channels in Mouse Primary Afferents in Naïve and Injured Conditions - Papalampropoulou-Tsiridou, Melina; Labrecque, Simon; Godin, Antoine G.; De Koninck, Yves; Wang, Feng (Frontiers in Cellular Neuroscience, 2020)
Injury and inflammation cause tissue acidosis, which is a common feature of various painful conditions. Acid-Sensing Ion channels (ASICs) are amongst the main excitatory channels activated by extracellular protons and expressed in the nervous system. Six transcripts of ASIC subunits including ASIC1a, ASIC1b, ASIC2a, ASIC2b, ASIC3 and ASIC4 are encoded by four genes (Asic1–4) and have been identified in rodents. Most ASIC subunits are present at substantial levels in primary sensory neurons of dorsal root ganglia (DRG) except for ASIC4. However, their expression pattern in DRG neurons remains largely unclear, mainly due to the lack of antibodies with appropriate specificity. In this study, we examined in detail the expression pattern of ASIC1-3 subunits, including splice variants, in different populations of DRG neurons in adult mice using an in-situ hybridization technique (RNAscope) with high sensitivity and specificity. We found that in naïve condition, all five subunits examined were expressed in the majority of myelinated, NF200-immunoreactive, DRG neurons (NF200+). However, ASIC subunits showed a very different expression pattern among non-myelinated DRG neuronal subpopulations: ASIC1 and ASIC3 were only expressed in CGRP-immunoreactive neurons (CGRP+), ASIC2a was mostly expressed in the majority of IB4-binding neurons (IB4+), while ASIC2b was expressed in almost all non-myelinated DRG neurons. We also found that at least half of sensory neurons expressed multiple types of ASIC subunits, indicating prevalence of heteromeric channels. In mice with peripheral nerve injury, the expression level of ASIC1a and ASIC1b in L4 DRG and ASIC3 in L5 DRG were altered in CGRP+ neurons, but not in IB4+ neurons. Furthermore, the pattern of change varied among DRGs depending on their segmental level, which pointed to differential regulatory mechanisms between afferent types and anatomical location. The distinct expression pattern of ASIC transcripts in naïve condition, and the differential regulation of ASIC subunits after peripheral nerve injury, suggest that ASIC subunits are involved in separate sensory modalities.